2021
DOI: 10.1002/anie.202016343
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Haliclonin A

Abstract: The total synthesis of haliclonin A was accomplished. Starting from 3,5‐dimethoxybenzoic acid, a functionalized cyclohexanone fused to a 17‐membered ring was prepared through a Birch reduction/alkylation sequence, ring‐closing metathesis, intramolecular cyclopropanation, and stereoselective 1,4‐addition of an organocopper reagent to an enone moiety. Reductive C−N bond formation via an N,O‐acetal forged the 3‐azabicyclo[3.3.1]nonane core. The allyl alcohol moiety was constructed by a sequence involving stereose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The data sets used in this study are shown in Additional file 1: Table S2. Finally, to further verify the performance of DeepSA for compounds with real synthetic pathways, we selected 18 compounds with complete synthetic pathways from the published literatures [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], which will be detailed introduced in the section of Results and Discussion.…”
Section: Collection Of Datasetsmentioning
confidence: 99%
“…The data sets used in this study are shown in Additional file 1: Table S2. Finally, to further verify the performance of DeepSA for compounds with real synthetic pathways, we selected 18 compounds with complete synthetic pathways from the published literatures [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], which will be detailed introduced in the section of Results and Discussion.…”
Section: Collection Of Datasetsmentioning
confidence: 99%
“…ZnX 2 , 25%; 2. NaBH 4 , 40%) to produce a mixture of regioisomers of olefinic double bonds, represented a notable and pioneering achievement for the biomimetic synthesis of the bicyclic core of halicyclamines. , In comparison to previous biomimetic approaches, , ,, the operationally simple, metal-free, and atom-economical dimerization developed herein allowed high-yielding and rapid access to an intricate dimeric scaffold bearing higher oxidation levels, which could offer a versatile platform for further synthetic manipulations leading to natural products. , …”
Section: Resultsmentioning
confidence: 99%
“…Precisely forging unsaturated molecular frameworks with the desired regio- and stereochemistry has always been a significant task and considerable challenge in organic synthesis. In this context, the metal-catalyzed hydroallylation of alkynes with allylic electrophiles or nucleophiles to construct skipped dienes continues to attract great attention, as the skipped diene scaffolds are valuable structural motifs in many bioactive natural products, 1 and are also specific building blocks in organic synthesis. 2 However, their development remains relatively sluggish compared with the well-established Alder-ene reactions, 3 due to the difficulty of controlling the regio- and stereoselectivity.…”
Section: Introductionmentioning
confidence: 99%